1994
DOI: 10.1152/ajpcell.1994.266.3.c809
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and functional properties of an epithelial K channel

Abstract: Expression cloning in Xenopus oocytes was used to identify a clone for a renal K channel. The clone, named ROMK2, was obtained from a cDNA library constructed in the plasmid vector pSPORT using size-selected poly(A)+ RNA from whole rat kidney. ROMK2 consists of 1,837 nucleotides, with an open reading frame of 1,116 bases predicted to code for a 372-amino acid peptide. The clone appears to be a splice variant of a recently reported K channel (ROMK1) from rat renal outer medulla (Ho, K.H., C.G. Nichols, W.J. Led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
110
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 0 publications
9
110
1
Order By: Relevance
“…However, a small though appreciable decline of channel activity occurs at lower concentrations of glibenclamide. This apparent sensitivity could be mediated by two separate effects: (i) Mg2+-independent channel rundown (32) and (ii) the expression of an endogenous peptide that serves as a sulfonylurea receptor (9). Previous voltage clamp studies demonstrated that application of glibenclamide produced an inconsistent effect on K+ currents inXenopus oocytes injected with ROMK2 cRNA (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a small though appreciable decline of channel activity occurs at lower concentrations of glibenclamide. This apparent sensitivity could be mediated by two separate effects: (i) Mg2+-independent channel rundown (32) and (ii) the expression of an endogenous peptide that serves as a sulfonylurea receptor (9). Previous voltage clamp studies demonstrated that application of glibenclamide produced an inconsistent effect on K+ currents inXenopus oocytes injected with ROMK2 cRNA (9).…”
Section: Resultsmentioning
confidence: 99%
“…Recently several inwardly rectifying potassium channels, which contain two transmembrane spanning domains characteristic of this rapidly expanding family of K+ channels, have been cloned (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). A potassium channel of renal origin (ROMK2), an alternative splice isoform of ROMK1 cloned from the outer medulla of the rat kidney (5,9,10), is an ATP-sensitive K+ channel (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This understanding has been fueled by the molecular identification of Na-K-2Cl cotransporter (NKCC2) (5,6), K ϩ secretory channel (ROMK) (7,8), and basolateral Cl Ϫ channel (ClC-K2) (9)(10)(11)(12) expressed in the TALH of mammalian kidney.…”
mentioning
confidence: 99%
“…Although the recombinant ROMK channel, as expressed in Xenopus oocytes, has been reported to by some investigators to exhibit sensitivity to the sulfonylurea K ATP channel blocker glibenclamide (43), we and others (44) have found that the response is modest, highly variable, and dependent on oocyte donor, suggesting the involvement of inconsistently expressed factors in the oocyte (44). Consequently, to study the effects of CFTR and NHERF on ROMK in the present study, we used a stock of frogs that was prescreened for lack of glibenclamide effects on expressed ROMK.…”
Section: Methodsmentioning
confidence: 76%